Effects of Fertiliser Application on Soil Properties of Smallholder Pepper Farm at Different Age Stand in Bau - Esther Sheren, anak Joseph (University Malaysia Sarawak, UNIMAS, 2015)
The application of fertilizer is depending on the requirement of the plant. As for pepper, fertilizer application is according to the maturity of the pepper vine. The difference of fertilizer for the young vine and mature vine is the ratio of N (Nitrogen), P (Phosphorus) and K (Potassium) content in the fertilizer. For younger vine which is below than three years old, the ration of NPK fertilizer is 12:12:17 as only focus on plant growth, and 15:15:15 for pepper vine more than three years old as focus more toward producing yield. The fertilizer applied also affected by the agronomic practices by the smallholder pepper farm. Agronomic practices are the method farmers incorporate into their pepper farm management systems to manage crops and improve soil quality. Therefore, the objective of this study is to determine the effects of fertilizer application on the soil properties in smallholder pepper farm in relation to different age stand. In this study, samples collected from fertilized and non-fertilized areas from each farm. This is to determine the fertilizer application is directly or indirectly affecting the soil properties and determine the significant differences between different age stand. Among the properties measured were pH and EC, soil organic matter (SOM) content, and available phosphorus (P). The result shows that among the different age stand, there is no significant differences between the properties except for available P from the fertilized area in the older pepper farm which is more than ten years old. The significant impact to that can be seen in the reducing amount of yield produced.